2006
DOI: 10.1002/jsfa.2684
|View full text |Cite
|
Sign up to set email alerts
|

Composition and bioactive factor content of cowpea (Vigna unguiculata L. Walp) raw meal and protein concentrate

Abstract: Analysis was done of the composition and bioactive factor content of whole meal, processed meal and protein concentrate from a cowpea cultivar (Vigna unguiculata L. Walp var. IT86D-719) grown in Yucatan, Mexico and of changes in these parameters after soaking and dehulling. Both meals had a high protein content (247.53 and 257 g kg −1 dry matter (DM) respectively). The protein concentrate was rich in protein (786 g kg −1 DM) and lipids (58.47 g kg −1 DM) and had an amino acid profile similar to that of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…The ash and crude fibre contents of the seem cultivars varied from 32.80 to 45.53 g kg −1 and from 21.90 to 28.90 g kg −1 respectively. These values are similar to those found in other legume seeds 21, 25, 26, 33–40. The variation in ash and fibre contents might be a characteristic of the soil in which the species was grown,2 since the seem cultivars were collected from various regions of Bangladesh.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The ash and crude fibre contents of the seem cultivars varied from 32.80 to 45.53 g kg −1 and from 21.90 to 28.90 g kg −1 respectively. These values are similar to those found in other legume seeds 21, 25, 26, 33–40. The variation in ash and fibre contents might be a characteristic of the soil in which the species was grown,2 since the seem cultivars were collected from various regions of Bangladesh.…”
Section: Resultssupporting
confidence: 84%
“…Moisture contents of the seem cultivars varied significantly ( P < 0.05). Similar moisture contents (71–117 g kg −1 ) have been reported in other legumes such as lima bean,2 cowpea,24, 25 Velvet bean26 and common bean,27, 28 and it has been proposed that this parameter might be related to the physical characteristics of the seed.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Considering a need to develop sources of concentrated plant proteins other than soybeans, the nutritive and functional properties of cowpea protein isolate were investigated. The composition, amino acid profile and bioactive/antinutritional factor content of whole meal, processed meal and protein concentrate prepared from cowpea have been reported by Olivera-Castillo et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to assume that these increases were observed because in both cases, the globulin and albumin fractions remained in the meal, while some fibre was removed in the form of the hull, leading to a relatively higher proportion of protein. In a study of chemical composition in whole and processed (soaking + dehulling) meals and protein concentrates from V. unguiculata seed, Olivera et al (2007) observed a not significant increase in protein content in the processed meal. In contrast, Wang et al (2009) found that in several lentil (Lens culinaris) varieties cooking and dehulling increased protein concentration, attributing this to loss of soluble solids such as minerals.…”
mentioning
confidence: 97%